2018
DOI: 10.1080/21645515.2017.1423154
|View full text |Cite
|
Sign up to set email alerts
|

Safety and biodistribution of sulfated archaeal glycolipid archaeosomes as vaccine adjuvants

Abstract: Archaeosomes are liposomes comprised of ether lipids derived from various archaea. Unlike conventional ester-linked liposomes, archaeosomes exhibit high pH and thermal stability. As adjuvants, archaeosomes can induce robust, long-lasting humoral and cell-mediated immune responses and enhance protection in murine models of infectious disease and cancer. Archaeosomes constituted with total polar lipids (TPL) of various archaea are relatively complex, comprising >10 different lipid compounds. Archaeosomes can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…Archaeal lipid adjuvants are a good potential candidate for use in combination with CPI's, as evidenced by their proven safety and efficacy in mice [19,44]. In multiple pre-clinical studies, they have been shown to activate antigen-specific CD8 + T cell responses [15,19,26,27] and generate protective immunity in tumor models, e.g., B16-OVA melanoma [7,13,19,23,26,27], and against multiple infectious diseases, e.g., H1N1 influenza [11], Listeria monocytogenes [7,12], Trypanosoma cruzi [13] and Mycobacterium tuberculosis [14]. When compared to commonly used commercial adjuvants, such as Poly(I:C) or Montanide, archaeal lipid vaccines were found to elicit equal or greater antigen specific CD8 + T cell-mediated cytotoxicity and IgG responses [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Archaeal lipid adjuvants are a good potential candidate for use in combination with CPI's, as evidenced by their proven safety and efficacy in mice [19,44]. In multiple pre-clinical studies, they have been shown to activate antigen-specific CD8 + T cell responses [15,19,26,27] and generate protective immunity in tumor models, e.g., B16-OVA melanoma [7,13,19,23,26,27], and against multiple infectious diseases, e.g., H1N1 influenza [11], Listeria monocytogenes [7,12], Trypanosoma cruzi [13] and Mycobacterium tuberculosis [14]. When compared to commonly used commercial adjuvants, such as Poly(I:C) or Montanide, archaeal lipid vaccines were found to elicit equal or greater antigen specific CD8 + T cell-mediated cytotoxicity and IgG responses [10].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to commonly used commercial adjuvants, such as Poly(I:C) or Montanide, archaeal lipid vaccines were found to elicit equal or greater antigen specific CD8 + T cell-mediated cytotoxicity and IgG responses [10]. SLA-based archaeosomes can also induce local cytokine production at the site of injection even in the absence of an antigen [19]. While cytokine production was not measured in this study, the use of empty SLA archaeosomes combined with anti-PD-1 and anti-CTLA-4 therapy (without OVA antigen) did not cause any increase in median survival compared to anti-PD-1 and anti-CTLA-4 alone (22.5 vs. 27 days, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional archaeosomal formulations consisted of liposomes formed from total polar lipids (TPL) derived from archaea such as the methanogen Methanobrevibacter smithii (MS). These archaeosomes were shown to effectively activate professional antigen-presenting cells [14][15][16] and generate robust cellular and humoral immune response to encapsulated antigen in both cancer and infectious disease models [11,12,17]. More recently, a novel simpler semi-synthetic archaeosome formulation composed of a sulfated disaccharide group covalently linked to the free sn-1 hydroxyl backbone of an archaeal core lipid (sulfated S-lactosylarchaeol, SLA), has been developed [18].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a novel simpler semi-synthetic archaeosome formulation composed of a sulfated disaccharide group covalently linked to the free sn-1 hydroxyl backbone of an archaeal core lipid (sulfated S-lactosylarchaeol, SLA), has been developed [18]. Archaeosomes formed with SLA alone or in combination with lactosylarchaeol (LA) retain a similar level of adjuvanticity to MS TPL archaeosomes, but consist of a simpler formulation with many advantages including consistency of production, reduced costs, and ease of synthesis [10,14,19]. A recent comparison of SLA to a wide panel of commercial adjuvants (e.g., aluminum salts, TLR agonists, and water/oil emulsions) when paired with the model antigens ovalbumin and HBsAg demonstrated that SLA archaeosome formulations had robust adjuvant activity that was superior to many of the other tested adjuvants [10].…”
Section: Introductionmentioning
confidence: 99%